Challenges of Fathers Encountered During Pregnancy and Childbirth - Ong Romero, Shiela Mae; Lanuzo, Heide (International Journal of Sustainability and Advanced Integrated Research, 2026)
This descriptive quantitative study investigated the challenges encountered by fathers during pregnancy and childbirth at Dr. Lorenzo P. Ziga Memorial District Hospital (DLPZMDH) in Tabaco City, Albay from July-September 2025. Using quota sampling, 100 biological fathers completed Likert-scale questionnaires assessing their roles, involvement levels, and barriers, analyzed through weighted means. Results showed high paternal role fulfillment (WM=3.41), involvement (WM=3.33), and challenges (WM=3.36), primarily financial struggles (3.77) and work conflicts (3.71). Anchored on Social Role Theory and Attachment Theory, findings reveal systemic gaps in father-inclusive maternal care. Recommendations target hospital protocols, policy reforms, and community interventions. This study examines the challenges faced by fathers during pregnancy and childbirth at Dr. Lorenzo P. Ziga Memorial District Hospital (DLPZMDH), Tabaco City, Albay, through a descriptive quantitative approach that identifies paternal roles, measures involvement levels, and proposes targeted support measures to bridge gaps in Philippine maternal healthcare systems where traditional gender norms, economic constraints, work-family conflicts, and mother-centric institutional practices limit fathers' active participation despite substantial evidence demonstrating benefits for maternal well-being, family cohesion, early infant bonding, and long-term child development outcomes.
Keywords: Paternal challenges; Pregnancy and childbirth; Father-inclusive maternal care; Paternal involvement; Philippines